Bees for the Future - Freitas, A.; Ferreira, C.; Campanário, C.; Freitas, F. (Open Schools Journal for Open Science, 2020)
In the academic year 2018/2019, students from Escola Secundária Jaime Moniz studied the importance of bees for the future using digital tools, platforms, and a simulator that represented the influence of the increase or decrease of flowers to the bee population and the other way around. They also established collaboration with their community to research their level of awareness, to collect knowledge from experts, and to analyze the health of the bee population in their island. For this, they collected information in a series of forms, which they shared in the Globallab platform with students from other parts of the world, gaining awareness of the relevance of problems at local and global levels. In the process, students visited a honey producer and organized a conference with the beekeeper. In the end, each group of students created a final product to present to the educational community, raising awareness of the problem studied. The products created were posters, leaflets, models, games, beds of honey plants, hives, and hotels for bees.